If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 + -9x = 5x + -7 Reorder the terms: 5 + 6x + -9x = 5x + -7 Combine like terms: 6x + -9x = -3x 5 + -3x = 5x + -7 Reorder the terms: 5 + -3x = -7 + 5x Solving 5 + -3x = -7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + -3x + -5x = -7 + 5x + -5x Combine like terms: -3x + -5x = -8x 5 + -8x = -7 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -8x = -7 + 0 5 + -8x = -7 Add '-5' to each side of the equation. 5 + -5 + -8x = -7 + -5 Combine like terms: 5 + -5 = 0 0 + -8x = -7 + -5 -8x = -7 + -5 Combine like terms: -7 + -5 = -12 -8x = -12 Divide each side by '-8'. x = 1.5 Simplifying x = 1.5
| 9r-7=8+4(r+5) | | -4-3x-x^2=0 | | x-6=20+8 | | 2y-16+xy-8x= | | y=x^2-2x-15 | | =4(-1)-8 | | 2x^2+9x= | | -9x-(-4x)= | | 31+4(c-1)=-(4c+5) | | 2x-6=7x+9 | | 2x+y=62.40 | | 28+2a=+7 | | 25v=-5 | | 3g-11=6+12(g+4) | | 50+5x=200+2x | | 3x-(-2x)= | | 2m-1=6+11(m+1) | | y=4(+5)-8 | | y=4(5)-8 | | y=4(4)-8 | | 3=-1+8x | | 6y-5x=0 | | 6x^2+7=0 | | 18-4y=-2(6+2y) | | y=4(-1)-8 | | 2y^2-2y+37=y^2+16 | | 6t+5(1-3t)= | | 2x^2-5x+2=(x-3)(x-2)+3x | | 4x+1=2x-17 | | -3+4m=2-3m | | N-12=50n+94 | | 2y=3x-8 |